Augmentation of light therapy in difficult-to-treat depressed patients: an open-label trial in both unipolar and bipolar patients - Camardese G (Dove Medical Press, 2015)
Giovanni Camardese,1 Beniamino Leone,1 Riccardo Serrani,1 Coco Walstra,1 Marco Di Nicola,1 Giacomo Della Marca,2 Pietro Bria,1 Luigi Janiri1 1Institute of Psychiatry and Psychology, 2Institute of Neurology, Catholic University of the Sacred Heart, Rome, Italy Objectives: We investigated the clinical benefits of bright light therapy (BLT) as an adjunct treatment to ongoing psychopharmacotherapy, both in unipolar and bipolar difficult-to-treat depressed (DTD) outpatients.Methods: In an open-label study, 31 depressed outpatients (16 unipolar and 15 bipolar) were included to undergo 3 weeks of BLT. Twenty-five completed the treatment and 5-week follow-up.Main outcome measures: Clinical outcomes were evaluated by the Hamilton Depression Rating Scale (HDRS). The Snaith–Hamilton Pleasure Scale and the Depression Retardation Rating Scale were used to assess changes in anhedonia and psychomotor retardation, respectively.Results: The adjunctive BLT seemed to influence the course of the depressive episode, and a statistically significant reduction in HDRS scores was reported since the first week of therapy. The treatment was well-tolerated, and no patients presented clinical signs of (hypo)manic switch during the overall treatment period. At the end of the study (after 5 weeks from BLT discontinuation), nine patients (36%, eight unipolar and one bipolar) still showed a treatment response. BLT augmentation also led to a significant improvement of psychomotor retardation.Conclusion: BLT combined with the ongoing pharmacological treatment offers a simple approach, and it might be effective in rapidly ameliorating depressive core symptoms of vulnerable DTD outpatients. These preliminary results need to be confirmed in placebo-controlled, randomized, double-blind clinical trial on larger samples. Keywords: light therapy, unipolar depression, bipolar depression, anhedonia, psychomotor dysfunction